Synthesis and properties of zirconium carbide film on graphite - Thanh, Vu Minh; Duong, Dang Van; Long, Le Kim; Nghia, Nguyen Duc (Vietnam Journal of Chemistry, 2014)
In this study, synthesis and properties of zirconium carbide on graphite will be introduced. CVD temperature and H2 flow affect properties of ZrC film. The increased temperature and increased size of crystal ZrC reduce flatness of the surface; contrarily, the increased flow of H2 and decreased size of crystal flatten the surface of porous film. The obtained results showed that CVD condition is suitable for producing uniform, consistent and flat ZrC film: temperature 1200 oC; H2 flow at 20 ml/min; flows of Ar, gas at 30, 80 ml/min, respectively; ZrCl4 8 g/time, CVD time 1 hour.  Phase components of ZrC film mainly consist of two principal phases ZrC and carbon. Film thickness ranges from 10.5-15.5 mm; film coating is uniform, non-crack, and highly compact and the film’s medium hardness is 1943 kG/mm2. Keywords: Zirconium carbide, film, graphite, CVD